Narrative analysis of Memri's English translations of Arabic editorials on Daesh / Nael F. M. Hijjo - Nael F. M. , Hijjo (2018)
The translation of political media narratives is a complex process wherein translation is regarded as a part of intercultural communication, and hence, translators are deemed competent in both the source and the target languages. The outcome of translation is shaped by the translators’ ideological, cultural, political and social knowledge and agenda (Valdeón, 2007). This study discusses the dynamic role of the translators in promoting certain ideologies and political agendas by presenting stories through the lens of an ideologically-laden meta-narrative. It compares the representation of ‘Daesh’ in the narratives of Arabic editorials with their English translations which are published online by the Middle East Media Research Institute (MEMRI). MEMRI is a Washington-based think tank and a pro-Israeli organisation, widely cited by Western, especially the US, leading media outlets. Original data consists of 46 Arabic editorials and their 25 English translations were collected for the purpose of this study. The study adopts the interdisciplinary narrative theory-informed analysis elaborated in Baker (2006) as its theoretical framework in order to analyse and explain the different embedded ideologies, values and cultures in the translations of the Arabic media editorials into English. In this context, narrative is a framework that seeks to legitimise, normalise and justify certain actions to the public. According to narrative theory, translators are considered as decisive participants in building knowledge as well as constructing political and social realities. The findings of this study suggest that narrativity features, selective appropriation in particular, are significant tools in the reconstruction of reality in translation. Through translation, MEMRI draws upon the meta-narrative of the ‘War on Terror’ in furthering its ideologically-laden agenda of terrorist Arabs and Muslims by publishing selective and decontextualized excerpts and reframed concepts such as Daesh (داعش ), Jihad (جهاد ), and Jizya (جزية ). MEMRI reframes the Arabic narratives on Daesh at three different levels; paratextual, contextual and textual. At the paratextual level, MEMRI is found to reframe the Arabic original narratives through titles, introductions (prefaces), images and their captions, in-text headings (internal titles), and endnotes and glossaries. At the contextual level, MEMRI reframes the thematic and episodic, and the temporal and spatial settings of the original narratives as well as the argumentative relationality; the construction of arguments. At the textual level, MEMRI re-framings of the original narratives are of two types: selective appropriation that includes omission and addition, and lexical and grammatical choices that includes lexical choice, grammatical shift and reorganisation of materials. Therefore, this study significantly draws attention to the critical role of translators and translation agencies in legitimising ideologically-reconstructed narratives in translation. It also highlights the impact of the value-laden reframing in negotiating the semantic and syntactic structures of the source narratives. It seeks the awareness of the public of the different rival circulated narratives by the media.